Refractory Status Epilepticus in Genetic Epilepsy—Is Vagus Nerve Stimulation an Option? - Specchio, Nicola; Ferretti, Alessandro; Pietrafusa, Nicola; Trivisano, Marina; Calabrese, Costanza; Carfì Pavia, Giusy; De Benedictis, Alessandro; Marras, Carlo Efisio; de Palma, Luca; Vigevano, Federico (Frontiers in Neurology, 2020)
Abstract Refractory and super-refractory status epilepticus (RSE, SRSE) are severe conditions that can have long-term neurological consequences with high morbidity and mortality rates. Usefulness of vagus nerve-stimulation (VNS) implantation during RSE has been documented within anecdotal cases and systematic reviews; however, use of VNS in RSE has not been widely adopted. We successfully implanted VNS in two patients with genetic epilepsy admitted in hospital for SRSE; detailed description of clinical findings and VNS parameters are provided. Our patients were implanted 25 and 58 days after status epilepticus (SE) onset and a stable remission of SE was observed after the seventh and tenth day after VNS implantation, respectively, without change in anti-seizure medication. We used a fast ramp -up of stimulation without evident side effects. Our results support consideration of VNS implantation as a safe and effective adjunctive treatment for SRSE.